Wind tunnel measurement and flow visualisation of soccer ball knuckle effect - Murakami, M.; Seo, K.; Kondoh, M.; Iwai, Y. (Sports Engineering, 2012)
Wind tunnel experiments were conducted, in particular focusing on slow unsteady variations of aerodynamic forces as a potential cause of the knuckle effect of a new soccer ball (Teamgeist) under non-spinning condition. The experiments included simultaneous measurements of the drag, the side force and the surface pressure on a ball surface, and the tuft visualisation to investigate the flow field behind a ball. Of particular interest was the erratic nature of the knuckle effect resulting from the unsteady movement of vortical wake structure in the supercritical Reynolds number regime. A simple 2-D numerical simulation of the ball flight trajectory was performed by taking into account the unsteady side force data measured in the present experiments.